Cytomorphological changes in the sputum after Radiation Therapy for patients with Bronchogenic Carcinoma - Al-baldawy, Mazin J. (Journal of the Faculty of Medicine Baghdad, 2007)
Background : Bronchogenic carcinoma is a common malignancy in iraq and radiotherapy is one of treatment methods for this disease . This study is cytopathological study dealing with sputum samples for bronchogenic carcinoma before and after radiotherapy . Objectives : To find morphological changes of the malignant cells as seen in cytopathological examination of the sputum after radiotherapy to the chest . Patients and Methods : Twenty five patients with a recent diagnosis of bronchogenic carcinoma presented to the Institute of Radiotherapy and Nuclear Medicine for the treatment in the period between 20th july 2004 and 25th june 2005 , sputum samples were obtained from these patients before and after they received radiation therapy to the chest (850 rad from cobalt 60 machine) .The malignant cells were studied by light microscope , cytological features of the malignant cells are compared before and after irradiation . Chi square test and P value were used as statistical methods for comparison of the changes in the malignant cells. Results : Squamous cell carcinoma was the most common type in this study. Cytoplasmic vacuolations in the malignant cells after radiation were not significant ( p value>0.05),nuclear changes following irradiation were significant (p value<0.05). Conclusion : malignant cells are affected by radiation with cytoplasmic and nuclear changes.